A arbitragem e os precedentes judiciais: observância, respeito ou vinculação? - Fioravanti, Marcos Serra Netto (2018)
The relationship between the judiciary and arbitration has always been one highly relevant topic in national and international doctrine. The edition of Law 13.129/2015, which amended the previous Law 9.307/96 (Arbitration Act), and the advent of the new Civil Procedure Code 2015, with significant changes regarding the regime of precedents, instigates the operators to seek a systemic balance that allows the adequacy between these two forms of conflict resolution. The judicial precedents have gained exacerbated importance in the recent legislative changes and due to that specialists discuss the approach and influence of the Anglo-Saxon system in Brazilian law, with origin in civil law. From this notorious importance given to judicial precedents and their effectiveness to jurisdictional system, we analyze the interference of judicial precedents and precedents in arbitration of law, especially in view of the importance that the Civil Procedure Code of 2015 has given to the so called by a new precedent system